2017 International Conference on Intelligent Informatics and Biomedical Sciences (ICIIBMS) 2017
DOI: 10.1109/iciibms.2017.8279720
|View full text |Cite
|
Sign up to set email alerts
|

Modern microwave thermometry for breast cancer

Abstract: The temperature of a malignant tumour is a universal indicator of the growth rate of the tumor. Tumor temperature can be used as a prediction of the benefit of individual therapies and in monitoring the efficacy of breast cancer treatment. This review provides a systematic analysis of the data available in the current literature on the role of microwave thermometry in risk estimation, the diagnosis of breast pathology and in assessing the effect of neoadjuvant therapy for breast cancer treatment.Various aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Considering that randomly selecting samples to expand the dataset will introduce more noise information, which will affect the recognition performance of the model, try to choose samples with high confidence to expand the existing dataset, and reduce the impact of noise on recognition. Therefore, this paper designs a more targeted sample selection strategy, which spans different mammography image datasets, selects high-quality samples (confidence by a set of classifiers), and makes full use of the pathological knowledge contained in new instances [ 33 , 34 ] to train a more effective and robust recognition model. To sum up, in the RMD model, the basic idea of the sample selection algorithm is to select a set of classifiers with the best performance and use a complex voting mechanism to choose samples from the source dataset; that is, the source dataset can be correctly classified by this set of classifiers.…”
Section: Rmd Model Frameworkmentioning
confidence: 99%
“…Considering that randomly selecting samples to expand the dataset will introduce more noise information, which will affect the recognition performance of the model, try to choose samples with high confidence to expand the existing dataset, and reduce the impact of noise on recognition. Therefore, this paper designs a more targeted sample selection strategy, which spans different mammography image datasets, selects high-quality samples (confidence by a set of classifiers), and makes full use of the pathological knowledge contained in new instances [ 33 , 34 ] to train a more effective and robust recognition model. To sum up, in the RMD model, the basic idea of the sample selection algorithm is to select a set of classifiers with the best performance and use a complex voting mechanism to choose samples from the source dataset; that is, the source dataset can be correctly classified by this set of classifiers.…”
Section: Rmd Model Frameworkmentioning
confidence: 99%
“…An important aspect that also affects the temperature is that cells in the tumoral zone use anaerobic glycolysis to generate energy (Warburg effect), which produces a significant amount of heat [37]. It has been shown that tumors with an accelerated growth rate, generally associated with malignant tumors in the pre-clinical stage, present a higher level of heat delivery than those that grow slowly [37,38].…”
Section: Angiogenesis and Glycolysis Processes Related To Temperature...mentioning
confidence: 99%
“…An important aspect that also affects the temperature is that cells in the tumoral zone use anaerobic glycolysis to generate energy (Warburg effect), which produces a significant amount of heat [37]. It has been shown that tumors with an accelerated growth rate, generally associated with malignant tumors in the pre-clinical stage, present a higher level of heat delivery than those that grow slowly [37,38]. Lymph node metastasis was also related with metabolic heat production, showing that, in the major cases, patients with tumors that present high levels of emissions of heat have developed lymph node metastasis [37].…”
Section: Angiogenesis and Glycolysis Processes Related To Temperature...mentioning
confidence: 99%
“…Outside of research, radio wave thermometry is currently rarely used in regular clinical applications. Studies of breast cancer have suggested that it may be beneficial to include microwave thermometry in screening programs and in examination of patients with breast pathologies [115]. However, based on the previously mentioned studies, it is not possible to determine the uncertainty of microwavederived internal temperatures and further research is warranted.…”
Section: Microwave Radiometry In Practicementioning
confidence: 99%